Evolution of inclusions with cerium addition and effects of C-containing rare earth inclusions on the toughness of ultra-high-strength structural steel. (7th February 2023) - Jiang, Yueyue; Li, Yongchao; Dai, Qingwei; Chai, Sensen; Li, Kejian
ABSTRACT: Ultra-high strength structural steels with Ce (cerium) content of 0, 0.0367, 0.0559 and 0.0792 wt.% respectively are prepared to study the effect of Ce addition on inclusions and the toughness of ultra-high-strength steel. The results show that the 0.0367 wt.% Ce can refine the size of oxides or sulfides to about 1 μm and improve the inclusion morphology to spherical, resulting in improved toughness of L-Ce steel. The number of inclusions in the H-Ce steel increases sharply, mainly due to the precipitation of C-containing rare earth inclusions. The rare earth carbides are hard and brittle phases, with the size of about 1 μm and a spherical shape. In addition to the increase in the number and size of inclusions, the reason for the deterioration of the toughness of H-Ce steel is that the C-containing rare earth inclusions are easily broken during hot rolling act as stress concentrators under impact loading.